Patient-reported outcomes in bilateral prophylactic mastectomy with breast reconstruction: A narrative review - Pavla Ticha; Andrej Sukop (Breast, 2024)
In women at high risk of developing breast cancer, bilateral prophylactic mastectomy (BPM) 1 significantly reduces the risk; simultaneously, breast reconstruction preserves body integrity. Given the complex and personal nature of such surgical procedures, patient assessment of satisfaction and health-related quality of life (HRQoL) 2 is essential in evaluation of surgical outcomes.With this review, we aim to organize the current knowledge on patient-reported outcomes (PROs) 3 in bilateral prophylactic surgery. Literature search was conducted using the databases Google Scholar, PubMed, and Web of Science to address the following questions, which can help clinicians and women undergoing the procedures navigate their healthcare decision-making process: How does BPM with reconstruction influence cancer-related distress? How does the surgery impact patient satisfaction and HRQoL? How do preoperative PROs differ from postoperative outcomes? Does the type of BPM and the type of reconstruction impact patient satisfaction and HRQoL? Furthermore, we summarize available patient-reported outcome measures (PROMs) 4 that can be administered to women undergoing BPM with reconstruction. In addition, we discuss possible future directions for PRO research in prophylactic breast surgery.